Zhishi Daozhi decoction alleviates constipation induced by a high-fat and high-protein diet via regulating intestinal mucosal microbiota and oxidative stress - Peng, Xinxin; Yi, Xin; Deng, Na; Liu, Jing; Tan, Zhoujin; Cai, Ying (Frontiers in Microbiology, 2023)
Background A growing body of evidence has demonstrated that a high-fat and high-protein diet (HFHPD) causes constipation. This study focuses on understanding how the use of Zhishi Daozhi decoction (ZDD) affects the intricate balance of intestinal microorganisms. The insights gained from this investigation hold the potential to offer practical clinical approaches to mitigate the constipation-related issues associated with HFHPD. Materials and methods Mice were randomly divided into five groups: the normal (MN) group, the natural recovery (MR) group, the low-dose ZDD (MLD) group, the medium-dose ZDD (MMD) group, and the high-dose ZDD (MHD) group. After the constipation model was established by HFHPD combined with loperamide hydrochloride (LOP), different doses of ZDD were used for intervention. Subsequently, the contents of cholecystokinin (CCK) and calcitonin gene-related peptide (CGRP) in serum, superoxide dismutase (SOD), and malondialdehyde (MDA) in the liver were determined. The DNA of intestinal mucosa was extracted, and 16S rRNA amplicon sequencing was used to analyze the changes in intestinal mucosal microbiota. Results After ZDD treatment, CCK content in MR group decreased and CGRP content increased, but the changes were not significant. In addition, the SOD content in MR group was significantly lower than in MLD, MMD, and MHD groups, and the MDA content in MR group was significantly higher than in MN, MLD, and MHD groups. Constipation modeling and the intervention of ZDD changed the structure of the intestinal mucosal microbiota. In the constipation induced by HFHPD, the relative abundance of pathogenic bacteria such as Aerococcus, Staphylococcus, Corynebacterium, Desulfovibrio, Clostridium, and Prevotella increased. After the intervention of ZDD, the relative abundance of these pathogenic bacteria decreased, and the relative abundance of Candidatus Arthromitus and the abundance of Tropane, piperidine, and pyridine alkaloid biosynthesis pathways increased in MHD group. Conclusion Constipation induced by HFHPD can increase pathogenic bacteria in the intestinal mucosa, while ZDD can effectively relieve constipation, reduce the relative abundance of pathogenic bacteria, and alleviate oxidative stress injury. In addition, high-dose ZDD can increase the abundance of beneficial bacteria, which is more conducive to the treatment of constipation.